2023
DOI: 10.1007/s00431-023-04921-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of myopia shift and myopia onset using 0.01% atropine in premyopic children — a prospective, randomized, double-masked, and crossover trial

Abstract: To evaluate the e cacy of 0.01% atropine eye drops in preventing myopia shift and myopia onset in premyopic children. A prospective, randomized, double-masked, placebo-controlled, crossover trial was conducted over 13 months. Sixty premyopic children aged 6-12 years with cycloplegic spherical equivalent refraction (SER) > -0.75 D and ≤ + 0.50 D in both eyes were assigned in a 1:1 ratio to receive one drop of 0.01% atropine or placebo once nightly for 6 months (period 1), followed by a 1-month recovery period. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22–0.36; p = 0.03) [ 58 ]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3 ): a noticeable difference between these studies can be observed in terms of sample size [ 107 – 109 ], study length and design [ 110 114 ], the age of the children studied [ 106 , 109 ], location of trial [ 115 117 ], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [ 110 , 114 , 118 , 119 ], and lastly their aims [ 109 , 111 , 112 , 120 ]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [ 109 , 110 , 114 , 115 , 118 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22–0.36; p = 0.03) [ 58 ]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3 ): a noticeable difference between these studies can be observed in terms of sample size [ 107 – 109 ], study length and design [ 110 114 ], the age of the children studied [ 106 , 109 ], location of trial [ 115 117 ], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [ 110 , 114 , 118 , 119 ], and lastly their aims [ 109 , 111 , 112 , 120 ]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [ 109 , 110 , 114 , 115 , 118 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3 ): a noticeable difference between these studies can be observed in terms of sample size [ 107 – 109 ], study length and design [ 110 114 ], the age of the children studied [ 106 , 109 ], location of trial [ 115 117 ], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [ 110 , 114 , 118 , 119 ], and lastly their aims [ 109 , 111 , 112 , 120 ]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [ 109 , 110 , 114 , 115 , 118 120 ]. Four studies were conducted in Europe [ 107 , 111 , 112 , 116 ], two in India [ 113 , 117 ], one in Iran [ 108 ], one in the USA [ 121 ], and one in Australia [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, few studies on myopia prevention were conducted because of ethical debates. Two recent studies explored the possibility of using atropine for myopia prevention and reported opposite findings. For 650-nm LLRL, a clinical trial reported a 54.1% reduction in incident myopia among children with premyopia within 12 months .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its significance, a lack of consensus remains regarding the precise definition of premyopia. In addition, the lack of standardized tools for risk stratification and management in these children complicates this scenario [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%